3-D printing of a metal material on another dissimilar metal base - Zhou, Xiaoyue (Nanyang Technological University, 2021)
Currently, how to achieve quality multi-metal (alloy) material printing is one research hotspot. To achieve strong interface bonding among different materials is the critical issue, considering both the implementation of additive manufacturing and other conventional manufacturing processes. The thermal incompatibility accompanying the material melting, cooling and solidification phase induces pores, cracks, brittle intermediate phase and other defects of parts fabricated, which degrade the bonding quality. Previous research done to solve these problems is summarized in this dissertation, including improvements in each element and step involved in the printing process such as the powder delivery device and method, the laser categories and its corresponding parameters, and the scanning strategies. The interface morphology of 3-D printed metallic part is an indicator of the part quality. To quantitatively evaluate the alloy-alloy interface quality, in this dissertation, the results of simulation carried out on CFD post software and actual experiments under the same working conditions are compared. Convective motion on different cross-sections can be observed, which further illustrates the underlying force state at different positions of the melt pool. A set of melt pool simulation schematics give a comprehensive view of 3-D printing of a metal material on a dissimilar metal base. Lastly, specific surface area growth rate is put forward to analyze the melt pool characteristics. The analysis and evaluation of the alloy-alloy interface can be utilized as an indicator to facilitate the reverse design of the metallic part, showing the connection between micro structure and macro behaviors, which provides a new thought to upgrade the 3-D printed metallic parts.